ANTIGENIC AND PROTECTIVE PROPERTIES OF EXPERIMENTAL ASSOCIATED VIRUS VACCINE AGAINST SHEEP POX AND GOAT POX - A. V. Konstantinov; S. K. Starov; V. I. Diev; N. V. Moroz; E. V. Kurnenkova; D. К. Basova; А. V. Kononov; K. Yu. Fedoseyev (Ветеринария сегодня)
Studies have been carried on antigenic and protective activity of the experimental associated vaccine containing, in the field vaccination dose, antigens of the attenuated ARRIAH strain of the sheep pox virus and ARRIAH 2003 strain of the goat pox virus in the ratio of 4.24 and 4.24 lg TCD50/cm3, 4.18 and 4.37 lg TCD50/cm3 and 4.37 and 4.18 lg TCD50/cm3 respectively, as well as monovalent vaccines with the infectious activity of these strains with a titer of 4.5 lg TCD50/cm3. Administration of the associated virus vaccine did not adversely affect the physiological state of the animals and was accompanied by the formation of viral neutralizing antibodies in protective titres that did not differ from antibody titers in the blood of sheep and goats during monovalent immunization. High levels of virus neutralizing antibodies in the range of (3.50 ± 0.50)–(4.05 ± 0.22) and (3.58 ± 0.08)–(4.00 ± 0.29) log2 respectively were determined in the blood serum of all sheep and goats vaccinated with associated vaccines. The antigenic activity of the associated vaccines for goats and sheep is almost identical. There were no negative effects on the antigenic activity of different ratios of attenuated strains of the sheep pox and goat pox virus in the inoculation dose. All sheep immunized with the monovalent vaccine against sheep and goat pox and associated virus vaccines, resisted the disease when challenged with a virulent sheep pox virus “Afghanistan” strain. Three sheep vaccinated with a monovalent vaccine against goat pox demonstrated a large local reaction, one sheep was diagnosed with generalized form of sheep pox.